Pengembangan Kampung Literasi sebagai Sarana untuk Meningkatkan Minat Baca Masyarakat yang Berkelanjutan pada Desa Kemuja Kabupaten Bangka - Fahrian, Farhan; Setyawati Hisyam , Endang; Apriyanti, Yayuk; Safitri, Ana; Pertiwi, Karin; Deftaristia, Violentine; Maharani, Anisyah; Veda Almer, Ezra; Mutiara, Ana (Indonesian Journal of Dedication and Educations, 2024)
The interest in learning and reading among the people of Kemuja Village is high, including its students. However, the availability of reading space for the public and students is still limited, including the type and number of reading books is not sufficient. The current condition of the Dahlia Community Reading Park (TBM) does not allow it to be used because it is not suitable and has been neglected. The high interest in reading among the people of Kemuja Village has great potential for the development of Kemuja Village as a Literacy Village pilot project in Bangka Regency. The aim of Village Development by the Bangka Belitung University Civil Engineering Student Association is to develop a Literacy Village in Kemuja Village through the Dahlia Community Reading Park. The method used to achieve the development of a Literacy village in Kemuja Village is through surveys/visits to the village government, youth organizations and TBM Founder, TBM Dahlia Socialization. The results obtained from Village Development activities, through renovations to the TBM, increasing the types and number of books, outreach to school children and the community, and reactivation of the TBM management by involving youth organizations, have further increased interest in reading at TBM Dahlia, so that it can develop Kemuja village as a Literacy Village.